Determination of Work Schedule Based on Employee Data Classification Using the Decision Tree Algorithm C4.5 Method - Effendi, Mas'ud; Ariani, Risna Dyah; Astuti, Retno (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis study aims to create a work shift scheduling system based on data classification, as well as to determine its level of accuracy and provide schedule recommendations. The method used was the Decision Tree Algorithm C4.5 which functions as a classification system to form a work shift schedule. The study included 128 employees, and a total of 43 training data were obtained from a 1/3 split of the dataset, then processed using RapidMiner 5.3 data mining software. Furthermore, the rule of decision tree calculation results was used to classify employee and shift formation on the web system based on PHP and MySQL. The attributes of the decision-maker consist of gender, health records, age, and work unit. The classification found 96 employees who occupy the afternoon shift and 32 for the night shift. System testing was carried out using K-fold cross-validation, which produced an average accuracy of 93.39%, with the highest found in the six-fold cross-validation of 95.35%. Two-shift scheduling was proposed on the web system with a work shift rotation in the form of a metropolitan plan (2-2-2 rota).Keywords: scheduling, Decision Tree C4.5, employee AbstrakPenelitian ini bertujuan untuk membuat sistem penjadwalan shift kerja berdasarkan klasifikasi data, mengetahui tingkat akurasi sistem penjadwalan shift kerja berdasarkan hasil klasifikasi, serta memberikan usulan jadwal shift kerja berdasarkan klasifikasi dari sistem penjadwalan kerja berbasis web. Metode yang digunakan adalah Decision Tree Algorithm C4.5 yang berfungsi sebagai pengklasifikasi untuk pembentukan penjadwalan shift kerja. Kebutuhan data dalam penelitian ini berjumlah 128 data tenaga kerja. Data training diperoleh melalui split 1/3 data tenaga kerja (43 data). Data training diolah menggunakan software data mining RapidMiner 5.3. Rule hasil perhitungan decision tree digunakan sebagai dasar klasifikasi tenaga kerja dan pembentukan shift pada sistem web berbasis PHP dan MySQL. Atribut pengambil keputusan terdiri dari atribut jenis kelamin, catatan kesehatan, usia, dan unit kerja. Hasil klasifikasi diperoleh 96 tenaga kerja yang menempati shift siang dan 32 tenaga kerja yang menempati shift malam. Pengujian sistem menggunakan K-fold cross validation menghasilkan rata-rata akurasi sebesar 93.39% dengan akurasi tertinggi pada six-fold cross validation sebesar 95.35%. Usulan rekayasa pada sistem web terdiri dari 2 shift kerja. Rotasi shift kerja mengadopsi tipe rotasi metropolitan plan (2-2-2 rota).Kata kunci: penjadwalan, Decision Tree C4.5, tenaga kerja